2015
DOI: 10.1002/aur.1534
|View full text |Cite
|
Sign up to set email alerts
|

Slowed Search in the Context of Unimpaired Grouping in Autism: Evidence from Multiple Conjunction Search

Abstract: In multiple conjunction search, the target is not known in advance but is defined only with respect to the distractors in a given search array, thus reducing the contributions of bottom-up and top-down attentional and perceptual processes during search. This study investigated whether the superior visual search skills typically demonstrated by individuals with autism spectrum disorder (ASD) would be evident in multiple conjunction search. Thirty-two children with ASD and 32 age- and nonverbal IQ-matched typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…It actually pays off to amplify the odd one out in this task. However, as a recent study by Keehn and Joseph (2016) pointed out, when the target is not known in advance people with ASD lose their advantage and actually perform worse, consistent with the current conception.…”
Section: Salience In Contextsupporting
confidence: 87%
“…It actually pays off to amplify the odd one out in this task. However, as a recent study by Keehn and Joseph (2016) pointed out, when the target is not known in advance people with ASD lose their advantage and actually perform worse, consistent with the current conception.…”
Section: Salience In Contextsupporting
confidence: 87%
“…While overt attention is essentially directed at a single target, cover attention analyzes several stimuli at once. A number of authors have also pointed to deficits in divided attention during complex events requiring the simultaneous analysis of various factors (Murray et al, 2005 ; Fletcher-Watson et al, 2008 ; Jaworski and Eigsti, 2015 ; Keehn and Joseph, 2016 ; Unruh et al, 2016 ; Bolis and Schilbach, 2017 ; Arora et al, 2022 ). Social events are the most demanding, as they require simultaneous attention to the internal state of the individual, to the environment, to the behaviors of others, and even to the hidden logic or real intentions behind such behaviors.…”
Section: Autism Theoriesmentioning
confidence: 99%
“…Next, one notable aspect of our study was that the target was defined on a trial-to-trial basis, rather than being predefined and fixed across several trials. Interestingly, using the same approach as the current experiment, Keehn and Joseph ( 2016 ) recently found that children with ASD were marginally worse than controls in conjunctive search. While we cannot rule out the possibility that this aspect of our experiment is relevant for the result, it is noteworthy that the above-mentioned previous study by Gregory and Plaisted-Grant ( 2016 ) on the relation between AQ and visual search in adults without autism failed to find an association despite using predefined and fixed targets.…”
Section: Discussionmentioning
confidence: 70%